Perspectives and Challenges of Microbial Application for Crop Improvement - Timmusk, Salme; Behers, Lawrence; Muthoni, Julia; Muraya, Anthony; Aronsson, Anne-Charlotte (Frontiers in Plant Science, 2017)
Global population increases and climate change pose a challenge to worldwide crop production. There is a need to intensify agricultural production in a sustainable manner and to find solutions to combat abiotic stress, pathogens and pests. Plants are associated with complex microbiomes, which are known to promote plant growth and stress tolerance, support plant nutrition and antagonize plant pathogens. The integration of beneficial plant-microbe and microbiome interactions may represent a promising sustainable solution to improve agricultural production. Commercial application of these microorganisms needs complex approaches, both in the technology in the field, and in marketing, extension education and ownership of the patent rights.